The tactics of the restoration of the movement of the upper limb after a postered traumatic brain injury by physical rehabilitation - Nadezhda Bogdanovska (Kazimierz Wielki University, 2021)
This article is a review conducted to analyze existing data on modern methods of physical rehabilitation of patients with brain damage. The loss of functional movement is a common consequence of the effects of traumatic brain injury, for which a wide range of interventions has been developed. Physical rehabilitation of persons with traumatic brain damage is currently based on evidence of neuroplasticity. The therapeutic method, which is based on neuroplasticity, leads to better motor and functional recovery than traditional methods. In addition, the restoration is permanent. Purpose: based on the study of the current state of the problem of restoration of motor function of the upper limb determine the feasibility of the use of CIMT therapy in the program of physical rehabilitation of individuals with the effects of traumatic brain injury. Methods of research: analysis of scientific literature, synthesis and generalization. Results. Limit-induced movement therapy (CIMT therapy) is a specialized approach that is used to increase the use of a limb affected by an acute cerebrovascular accident or traumatic brain damage. CIMT therapy is based on a targeted approach to improve the functional use and control of the affected limb. A number of studies of neuro-visualization and transcranial magnetic stimulation have shown that the use of CIMT therapy can cause massive cortical reorganization. From the point of view of research on the effectiveness of this therapeutic intervention, the high quality of randomized controlled studies have shown a positive effect on patients with the effects of brain damage. However, the functional benefits are largely limited to those patients who have active movements in the wrist and knuckles, as well as from the beginning of therapeutic measures. It has been determined that patients who use CIMT therapy 3-9 months after brain damage achieve a greater functional benefit than using therapy in delayed treatment. Conclusions: It has been found that the effects of CIMT therapy and its modified versions improve movements, not only remain stable for several months after completion of therapy, but also contribute to the improvement of everyday functional tasks.